CORAK TAFSIR MAQA - Nisa, Nur Maliyah Nisa Mardiyah; Fa'id, Muhammad Nur Fawaid As'ad (Qolamuna : Jurnal Studi Islam, 2025)
Book Nazm al-Durar fi Tanasib al-‘Ayat wa al-Suwar by al-Burhan al-Din ‘Abi alH{ayan ‘Ibrahim b. ‘Umar al-Biqa’i has various style of interpretation. One of them is the maqas}id pattern. Study of maqas}id patterns in the book Naz}m al-Durar fi Tanasib al-‘Ayat wa al-Suwar through several methods carried out by al-Biqa’i. Therefore, this article will review the method used by al-Biqa’i with maqas}id style in his interpretation. This research uses qualitative research methods with library research data collection techniques. There are two sources used, namely primary sources which use the books Naz}m al-Durar fi Tanasib al-‘Ayat wa al-Suwar and secondary sourceswhich use books and journal related to the topic of discussion. This research found that al-Biqa’i used munasabah science in explaning his maqas}id in the Qur’an. This shows that in his interpretation, al-Biqa’i has included each maqas}id in his surah and studied them using the munasabah method. Apart from the maqa>s}id of each surah found, there are also advantages of each surah. The two are interrelated because the priority of each surah is in accordance with the purpose of the surah (maqa>s}id of surah). Keywords : Maqas}id Tafsir Style, Book Naz}m al-Durar fi Tanasib al-‘Ayat wa al-Suwar, al-Biqa’i